Concept mapping methodology and community-engaged research: A perfect pairing. (February 2017) - Vaughn, Lisa M.; Jones, Jennifer R.; Booth, Emily; Burke, Jessica G.
Highlights: Concept mapping methodology as refined by Trochim et al. is uniquely suited to engage communities in all aspects of research. We focus on articles describing high community engagement and the associated community outcomes/benefits and methodological challenges. The results of this literature review enhance our understanding of how concept mapping can be used in direct collaboration with communities. Community-engaged concept mapping methodology has many potential benefits for both researchers and communities. Abstract: Concept mapping methodology as refined by Trochim et al. is uniquely suited to engage communities in all aspects of research from project set-up to data collection to interpreting results to dissemination of results, and an increasing number of research studies have utilized the methodology for exploring complex health issues in communities. In the current manuscript, we present the results of a literature search of peer-reviewed articles in health-related research where concept mapping was used in collaboration with the community. A total of 103 articles met the inclusion criteria. We first address how community engagement was defined in the articles and then focus on the articles describing high community engagement and the associated community outcomes/benefits and methodological challenges. A majority (61%; n = 63) of the articles were classified as low to moderate community engagement and participation while 38% (n = 39) of the articles were classified as high community engagement and participation. The results of this literature review enhance our understanding of how concept mapping can be used in direct collaboration with communities and highlights the many potential benefits for both researchers and communities.